Climate and climate sensitivity to changing CO2 on an idealized land planet. (13th December 2014) - Becker, Tobias; Stevens, Bjorn
Abstract The comprehensive general circulation model ECHAM6 is used in a radiative‐convective equilibrium configuration. It is coupled to a perfectly conducting slab. To understand the local impact of thermodynamic surface properties on the land‐ocean warming contrast, the surface latent heat flux and surface heat capacity are reduced stepwise, aiming for a land‐like climate. Both ocean‐like and land‐like RCE simulation reproduce the tropical atmosphere over ocean and land in a satisfactory manner and lead to reasonable land‐ocean warming ratios. A small surface heat capacity induces a high diurnal surface temperature range which triggers precipitation during the day and decouples the free troposphere from the diurnal mean temperature. With increasing evaporation resistance, the net atmospheric cooling rate decreases because cloud base height rises, causing a reduction of precipitation. Climate sensitivity depends more on changes in evaporation resistance than on changes in surface heat capacity. A feedback analysis with the partial radiation perturbation method shows that amplified warming over idealized land can be associated with disproportional changes in the lapse rate versus the water vapor feedback. Cloud feedbacks, convective aggregation, and changes in global mean surface temperature confuse the picture.